Effect of drought on photosynthetic apparatus, activity of antioxidant enzymes, and productivity of modern winter wheat varieties - V. V. Morgun; O. O. Stasik; D. A. Kiriziy; O. G. Sokolovska-Sergiienko (Regulatory Mechanisms in Biosystems, 2019)
The response of modern winter wheat varieties to soil drought was studied with aim of phenotyping their drought tolerance characteristics and identification of the most informative indices that may be suitable for use in breeding programs. Plants of winter bread wheat (Triticum aestivum L.) varieties Podolyanka, Khurtovyna, Vinnychanka and Prydniprovska were grown in a pot experiment. The soil moisture for control plants was maintained at a level of 70% of field capacity (FC) throughout the vegetative stage. At the flowering, watering of the treated plants was stopped to reduce the soil moisture to a level of 30% FC and then this soil moisture level was maintained for 10 days. After that, the irrigation of the treated plants was restored to the level of control. It was found that in the flag leaf under drought condition, the chlorophyll content, net CO2 assimilation rate, and transpiration rate decreased, while the leaf water deficit, the ratio of photorespiration to CO2 assimilation, and the activity of chloroplasts antioxidant enzymes (superoxide dismutase and ascorbate peroxidase) increased. The ten-day drought significantly reduced the grain yield from the plant. Calculations of the relative changes in the physiological parameters of treated plants as compared to the control were the most informative for the differentiation of varieties for drought tolerance. Relative changes in the content of chlorophyll in the flag leaf under drought and reduction in the total biomass of the plant closely correlated with a decrease in grain productivity (r = 0.92 and r = 0.96 respectively). There was also a significant correlation of grain productivity with a decrease in the NAR measured in the period of drought (r = 0.68). Therefore, the maintenance of the photosynthetic function of plants under conditions of insufficient water supply plays a determinant role in reducing the grain productivity losses. The relative changes in the chlorophyll content and CO2 assimilation rate in plants subjected to drought as compared to control may be used as markers of drought tolerance of genotypes for genetic improvement of wheat by conventional breeding and biotechnological methods.